2021
DOI: 10.3390/molecules26102844
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Factors in Rosuvastatin-Treated Men with Mixed Dyslipidemia and Early-Onset Androgenic Alopecia

Abstract: Men with early-onset androgenetic alopecia are characterized by hormonal profiles similar to those observed in women with polycystic ovary syndrome. The purpose of this research was to investigate levels of cardiometabolic risk factors in 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA)-treated men with early-onset androgenic alopecia. We studied two matched rosuvastatin-treated groups of men with mixed dyslipidemia: subjects with early-onset androgenic alopecia (group A) and subjects with normal hair growth (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
5
2
Order By: Relevance
“…This explanation seems, however, less likely than the previous ones. Contrary to previous studies of our research group [43,44], at entry there were no correlations between HOMA1-IR and uric acid, fibrinogen and homocysteine, while correlations with hsCRP and 25-hydroxyvitamin D were weaker than correlations between both these factors and other cardiometabolic risk factors. Moreover, there were no relationships between changes in uric acid, hsCRP, fibrinogen, homocysteine and 25-hydroxyvitamin and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This explanation seems, however, less likely than the previous ones. Contrary to previous studies of our research group [43,44], at entry there were no correlations between HOMA1-IR and uric acid, fibrinogen and homocysteine, while correlations with hsCRP and 25-hydroxyvitamin D were weaker than correlations between both these factors and other cardiometabolic risk factors. Moreover, there were no relationships between changes in uric acid, hsCRP, fibrinogen, homocysteine and 25-hydroxyvitamin and insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, there were no relationships between changes in uric acid, hsCRP, fibrinogen, homocysteine and 25-hydroxyvitamin and insulin sensitivity. This discrepancy between results of the present and of previous ones may be associated with greater insulin sensitivity in euthyroid patients with Hashimoto's thyroiditis than in subjects with hyperprolactinemia [43] or early onset androgenic alopecia [44].…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Krysiak et al [ 22 ] have reported that rosuvastatin, a 3-hydroxy-3-methyl-glutaryl-CoA r eductase inhibitor, strongly lowering total and LDL cholesterol levels and highly effective in the primary and secondary prevention of coronary artery disease and stroke [ 23 ], deteriorated insulin sensitivity and induced less pronounced cardiometabolic effects in men with early-onset male-pattern hair loss than in subjects with normal hair growth. Similarly, both hypotensive and pleiotropic effects of lisinopril, one of the most commonly used angiotensin-converting enzyme inhibitors [ 24 ], in hypertensive individuals were less pronounced if they had coexisting early-onset androgenic alopecia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in line with previous findings showing that individuals with early-onset androgenic alopecia benefited to a lesser degree from treatment with metformin and rosuvastatin. 18,21 Therefore, it seems that early-onset male-pattern hair loss should not be perceived merely as a cosmetic defect, as it seems to be an under-recognized entity with important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 With common genetic background and similarities in metabolic and hormonal profiles, early-onset androgenic alopecia is regarded by some authors as the male equivalent of polycystic ovary syndrome. 14,20 The results of recent studies suggest that cardiometabolic effects of rosuvastatin in men with mixed dyslipidemia, 21 and the impact of metformin on glucose homeostasis in men at high risk for type 2 diabetes, 18 are less pronounced in the case of coexisting early-onset androgenic alopecia. Although hyperprolactinemia and early-onset male-pattern hair loss may exert an additive unfavorable effect on cardiometabolic risk, no study has been carried out to investigate dopamine agonists in patients with the simultaneous presence of both these conditions.…”
mentioning
confidence: 99%